Study of vertical bending vibration behavior of continuous prestressed concrete box girders with corrugated steel webs. Issue 6 (June 2016) - Ji, Wei; Deng, Lu; Liu, Shizhong; Lin, Pengzhen
Prestressed concrete girders with corrugated steel webs have received considerable attention in the past two decades due to their light self-weight and high prestressing efficiency. Most previous studies were focused on the static behavior of corrugated steel webs and simple beams with corrugated steel webs. The natural frequencies are very important characteristics when evaluating the dynamic responses of a bridge under external loads; however, very few studies have been conducted to investigate the dynamic behavior of full prestressed concrete girders or bridges with corrugated steel webs, and no simple formulas are available for estimating the natural frequencies of prestressed concrete girder bridges with corrugated steel webs. In addition, experimental work on full-scale bridges or scale bridge models is very limited. In this article, formulas for predicting the vertical bending vibration frequencies of prestressed concrete box girders with corrugated steel webs are proposed based on Hamilton's energy variational principle. A one-tenth scale model is developed for an existing prestressed concrete box-girder bridge with corrugated steel webs. The frequencies predicted by the proposed formulas are compared to the finite element analysis results and also the experimental results from the scale bridge model. Good agreement is achieved between these results, indicating that the proposed formulas can provide a reliable and efficient tool to predict the vertical bending vibration frequencies of prestressed concrete box-girder bridges with corrugated steel webs.